2000
DOI: 10.1021/jp994471n
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the O(3P) + N2O Reaction. 2. Interpretation and Recommended Rate Coefficients

Abstract: The reaction O( 3 P) + N 2 O is important to models of NO x pollutant and propellant chemistry and to the understanding of the thermal decomposition of N 2 O, which has historically played a key role in the development of unimolecular reaction theory. The reaction has two important product channels: ). Rate coefficients of these reactions have been the subject of several reviews. However, clear reasons why many of the evaluated, nonretained data differ from recommendations have not previously been known. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
81
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 51 publications
(93 citation statements)
references
References 58 publications
11
81
1
Order By: Relevance
“…The rate constant of the N 2 O + Ar → N 2 + O + Ar reaction could thus be deduced during all the observation time at temperatures above 1900 K. At temperatures higher than 2500 K, the nitrous oxide decomposition rate was too fast to be accurately evaluated. Then, the upper temperature for this study was limited to 2500 K. At temperatures lower than 1900 K, although the rate constant for the studied reaction has been considered to be in the low-pressure limit for pressures ≤600 kPa [7,8], the present experiments showed that, at pressures above approximately 300 kPa, the unimolecular decomposition of N 2 O had to be taken into account for modeling determined by Meagher and Anderson [9] determined by Davidson et al [5] recommended by Tsang and Herron [12] without N 2 O+O elementary reactions precisely the O atom concentration toward the low temperatures (Fig. 9).…”
Section: Experimental Rate Coefficientsmentioning
confidence: 93%
See 3 more Smart Citations
“…The rate constant of the N 2 O + Ar → N 2 + O + Ar reaction could thus be deduced during all the observation time at temperatures above 1900 K. At temperatures higher than 2500 K, the nitrous oxide decomposition rate was too fast to be accurately evaluated. Then, the upper temperature for this study was limited to 2500 K. At temperatures lower than 1900 K, although the rate constant for the studied reaction has been considered to be in the low-pressure limit for pressures ≤600 kPa [7,8], the present experiments showed that, at pressures above approximately 300 kPa, the unimolecular decomposition of N 2 O had to be taken into account for modeling determined by Meagher and Anderson [9] determined by Davidson et al [5] recommended by Tsang and Herron [12] without N 2 O+O elementary reactions precisely the O atom concentration toward the low temperatures (Fig. 9).…”
Section: Experimental Rate Coefficientsmentioning
confidence: 93%
“…Temperature and pressure behind the reflected shock wave were computed from the incident shock speed, which was measured by piezoelectric pressure gauges. [3] with k N 2 O+Ar suggested by Dean and Bozzelli [13] with k N 2 O+Ar determined by Röhrig et al [7] [3] with k N 2 O+Ar suggested by Dean and Bozzelli [13] with k N 2 O+Ar determined by Röhrig et al [7] [3] with k N 2 O+Ar suggested by Dean and Bozzelli [13] with k N 2 O+Ar determined by Röhrig et al [7] Meagher and Anderson [9] Baulch et al [14] Davidson et al [5] Dean and Bozzelli [13] Röhrig et al [7], Hanson and Salimian [11], Tsang and Herron [12] Zuev and Starikovskii [4] The optical detection technique for measuring O atom concentration was an emission line absorption method. A microwave-excited discharge lamp that contained a flowing mixture of 1% O 2 in He maintained at a pressure of 1.4 kPa was used as light source.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction of N2O with an O atom can form NO in both the combustion and the thermal decomposition of N2O. Many experimental 11,12 and theoretical 13,14 studies have focused on this interaction. These works suggested that the activation energy of the reaction is about 115.8 kJ/mol.…”
Section: Introductionmentioning
confidence: 99%